2020
DOI: 10.2471/blt.20.255695
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CoronaTracker: World-wide COVID-19 Outbreak Data Analysis and Prediction

Abstract: DISCLAIMER This paper was submitted to the Bulletin of the World Health Organization and was posted to the COVID-19 open site, according to the protocol for public health emergencies for international concern as described in Vasee Moorthy et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
183
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(205 citation statements)
references
References 11 publications
1
183
0
2
Order By: Relevance
“…COVID-19 as an infectious disease that remains ambiguous; an accurate prediction can only be obtained when the pandemic ends ( Hamzah, et al, 2020 ). The pandemic is substantially influenced by each country’s policy and social responsibility ( Anderson, Heesterbeek, Klinkenberg, & Hollingsworth, 2020 ).…”
Section: Authors’ Claims and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 as an infectious disease that remains ambiguous; an accurate prediction can only be obtained when the pandemic ends ( Hamzah, et al, 2020 ). The pandemic is substantially influenced by each country’s policy and social responsibility ( Anderson, Heesterbeek, Klinkenberg, & Hollingsworth, 2020 ).…”
Section: Authors’ Claims and Discussionmentioning
confidence: 99%
“…The situational reports of the World Health Organisation’s ( WHO ) statistics have indicated that the number of confirmed cases exceeds 37,109,851 , and the number of deaths exceeds 1,070,355 worldwide ( WHO, 2020 ). Accurate insights into COVID-19 can only be obtained when the pandemic ends as literature and statistics are proliferating, and keeping data updated is nearly impossible ( Hamzah, et al, 2020 ). On 28 February 2020 , the WHO launched emergency protocols in all medical and public health systems because of the severity and risks of COVID-19 ( Epidemiol, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Each neuron has a set of weights where each one is multiplied by one input into the neuron, these are then summed to form the output from the neuron after it has been fed through the activation function. Deep neural networks often require big data and huge numbers of training data to be able to give performing results [9].…”
Section: Deep Neural Network (Dnn)mentioning
confidence: 99%
“…In fact, our goal here is to reuse the models already built and trained on china series times dataset to predict COVID-19 outbreak in Tunisia. Our motivation is to increase the size of training data as DNN often requires huge numbers of training data [9]. So in this augmented prediction, China data are used as training data and Tunisia data are considers as Test data.…”
Section: Augmented Prediction: From China To Tunisiamentioning
confidence: 99%
“…Since COVID-19 was first detected on 25 January 2020 in Malaysia, over 6,000 people have been infected by the virus, and a total 113 deaths has been reported as of 18 May 2020 [3]. In order to curb this pandemic, Malaysia has instituted several non-pharmaceutical intervention (NPI) strategies including the Movement Control Order (MCO) which was first implemented on 18 March 2020.…”
Section: Introductionmentioning
confidence: 99%